The relationship between underage initiation of selling sex and depression among female sex workers in Eswatini - Grosso, Ashley; Fielding-Miller, Rebecca; Matse, Sindy; Sithole, Bhekie; Baral, Stefan (Frontiers in Psychiatry, 2023)
Background: Minors who sell sex are likely to have complex mental health needs that may persist into adulthood. This topic is understudied in sub-Saharan Africa. This study hypothesized that adult female sex workers in Eswatini who started selling sex as minors have a higher prevalence of depression than those who started as adults. We also examined correlates of depression and underage initiation of selling sex, including stigma and condom-related behaviors. Methods: From October-December 2014, women aged 18 or older who sold sex in the past 12 months in Eswatini were recruited through venue-based sampling. Participants completed a survey including the 9-item Patient Health Questionnaire (PHQ-9) and a question about the age at which they first sold sex for money. T-tests, χ2 tests and multivariable logistic regression were used to assess associations. Results: Overall, 43.1% of participants (332/770) had probable depression, and 16.6% (128/770) started selling sex as minors under the age of 18. Over half (55.5%, 71/128) of those who started selling sex as minors had depression. This was significantly higher than the 40.7% (261/642) prevalence of depression among participants who started selling sex as adults (p=0.002). After adjusting for confounders, female sex workers who started selling sex as minors had higher odds of depression than those who started as adults (adjusted odds ratio 1.70, 95% confidence interval 1.11-2.60). Conclusion: Results highlight the need for trauma-informed and adolescent-friendly mental health services in settings free of stigma toward female sex workers in Eswatini.